2018
DOI: 10.1088/1361-648x/aac96e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external magnetic field and out-of-plane strain on magneto-optical Kerr spectra in CrI3 monolayer

Abstract: Magnetic semiconductors based on two-dimensional (2D) crystals have attracted attention owing to their intrinsic ferromagnetism and have potential for spintronic devices. Here, full-potential linearized augmented plane wave plus local orbitals method is used to explore the structural, electronic, magnetic, and magneto-optical properties of CrI monolayer. Our first-principles calculations show that CrI monolayer is a ferromagnetic indirect semiconductor with spin-up and spin-down band gaps of 1.23 and 1.90 eV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Taking SOC effects into account, the total energies E m//a and E m//c can be achieved through noncollinear calculations, and then the MAE can be evaluated. Consistent with the previous calculations 12,18,19,21 and experimental results, 13,17 because of the strong SOC in the heavier iodine ions, 17 the easy axis for monolayer CrI 3 is outplane with MAE 0.73 meV per Cr atom.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Taking SOC effects into account, the total energies E m//a and E m//c can be achieved through noncollinear calculations, and then the MAE can be evaluated. Consistent with the previous calculations 12,18,19,21 and experimental results, 13,17 because of the strong SOC in the heavier iodine ions, 17 the easy axis for monolayer CrI 3 is outplane with MAE 0.73 meV per Cr atom.…”
Section: Resultssupporting
confidence: 88%
“…16,18 The magnetism arises from the partially lled d orbitals of the Cr 3+ ion, and the magnetocrystalline anisotropy favours an out-plane spin orientation. 12 It has been demonstrated that the magnetic properties of CrI 3 can be controlled by strain, [19][20][21][22][23] electric elds 24-28 and magnetic elds. 21,29 To combine the advantages of two different 2D materials, stacking them into a heterostructure has been proven to be an effective way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, both the CBM and VBM occurs at the G-point of Brillouin zone, showing a semiconducting behaviour with the direct bandgap of 1.14 eV that is consistent with the previously reported results. [24][25][26] Fig. 5b presents the spindependent electronic band structure of the O-attached CrI 3 monolayer.…”
Section: Electronic Structurementioning
confidence: 99%
“…It has been theoretically demonstrated that a silicene monolayer exhibits maximum of 8° and 13° respectively for Faraday and Kerr rotations in terahertz regime . Other 2D materials with MO properties that have been studied so far include phosphorene, molybdenum disulfide (MoS 2 ), tungsten diselenide (WSe 2 ), chromium triiodide (CrI 3 ), and Cr 2 Ge 2 Te 6 …”
Section: Magnetooptical Materialsmentioning
confidence: 99%